ECOLOGICAL PROBLEMS OF THE KARSHI DESERT: HISTORICAL ANALYSIS (Western European Journal of Historical Events and Social Science, 2024)
In the article, the author examines the discharge of Amu Darya waters into the Karshi Desert and its ecological consequences. The study highlights the environmental issues that arose in the desert as a result of the exploitation of the Karshi Desert during the Soviet period